1976
DOI: 10.3181/00379727-151-39146
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Salicylic Acid on Metabolism and Potassium Ion Content in Yeast

Abstract: Numerous studies have shown that salicylates markedly alter metabolism, enzymic activity, and cell growth (1 -5). In both human erythrocytes (6) and molluscan neurones (7), salicylate increases the permeability of the cell membrane to K+ ion; in the latter study it was shown that salicylate simultaneously lowered the permeability to chloride ion. In the neuronal studies (7), these changes resulted in an increased potential difference across the cell membrane and the authors postulated that salicylate analgesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Tillberg (1970) found that salicylic acid at concentrations of 10 −6 –10 −3 mol l −1 (0·138–138 mg l −1 ) decreased the phosphorus uptake of the alga Scenedesmus . Meanwhile, Scharff and Perry (1976) reported that under anaerobic conditions, at a low pH and 30°C, yeast lost K + ions in the presence of salicylic acid and glucose utilization was inhibited. Thus, they concluded that a fundamental action of this compound in many organisms was to reduce the K + content in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tillberg (1970) found that salicylic acid at concentrations of 10 −6 –10 −3 mol l −1 (0·138–138 mg l −1 ) decreased the phosphorus uptake of the alga Scenedesmus . Meanwhile, Scharff and Perry (1976) reported that under anaerobic conditions, at a low pH and 30°C, yeast lost K + ions in the presence of salicylic acid and glucose utilization was inhibited. Thus, they concluded that a fundamental action of this compound in many organisms was to reduce the K + content in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested the different results might be due to differences between species or pH of the absorption medium. Scharff and Perry (14) reported that pH of the bathing medium affects K+ efflux from yeast cells in the presence of SA. In a preliminary publication (7), we reported a similar effect of pH and SA on K+ efflux from oat roots.…”
mentioning
confidence: 99%
“…P CCW12 was engineered to be salicylate-responsive by introducing two copies of the cmeO operator sequence 11 bp downstream of the TATA box consensus sequence TATA(A/T)A(A/T)(A/G) 43 found at −133–125 nt relative to the transcription start site, thereby generating P CCW12O and the sensor strain ( Figure 2 A). Due to the toxicity of salicylate to S. cerevisiae , 44 , 45 all experiments were conducted at a lower yeast culture dilution factor and were measured after 8 h. GFP fluorescence outputs of the control and sensor strains measured by flow cytometry showed a marked drop in fluorescence upon inserting cmeO , which in turn increased by adding increasing concentrations of salicylate to the culture media, reaching up to ∼4.3-fold induction in 2.5 mM salicylate ( Figure 2 B). This data shows that, in a manner similar to our E. coli genetic circuit, CmeR functions as a transcription repressor in S. cerevisiae , and is inducible by salicylate.…”
Section: Resultsmentioning
confidence: 99%